Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/1753-0407.12570
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and cardiometabolic risk factors in Cambodia: Results from two screening studies

Abstract: In Cambodia, diabetes rates are high among urban residents and undiagnosed diabetes is highest among rural residents. A country-wide public health response is urgently needed; as development continues, rates of diabetes are expected to rise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…The present study’s results for the prevalence of hypertension and diabetes and dyslipidemia were similar or higher than the prevalence of hypertension (34.7%) and diabetes (9.6%) in urban Cambodia in 2012, which was reported by Wagner et al in 2018 [ 6 ]. Moreover, the prevalence was higher than the prevalence of hypertension (29.7%) and diabetes under treatment (5.6%) in urban Cambodia reported by the STEPS survey in 2010 [ 5 ].…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The present study’s results for the prevalence of hypertension and diabetes and dyslipidemia were similar or higher than the prevalence of hypertension (34.7%) and diabetes (9.6%) in urban Cambodia in 2012, which was reported by Wagner et al in 2018 [ 6 ]. Moreover, the prevalence was higher than the prevalence of hypertension (29.7%) and diabetes under treatment (5.6%) in urban Cambodia reported by the STEPS survey in 2010 [ 5 ].…”
Section: Discussionsupporting
confidence: 80%
“…A study published in 2010 examined the risk factors for NCDs in Cambodia and reported the prevalence of overweight and obesity as 15.4% and 1.9%, respectively, which was higher in women, whereas that of hypertension and diabetes were 11.2% and 2.9%, respectively, and were significantly higher in urban areas than in rural areas [ 5 ]. Wagner et al reported a higher prevalence of diabetes and obesity in the urban areas of Cambodia [ 6 ]. One of the main reasons for the high prevalence of metabolic risk factors in urban areas is the change in the living environment due to urbanization, which is caused by economic development [ 7 ].…”
Section: Introductionmentioning
confidence: 99%